Numerical Simulation of Multi-point Corona Discharge Characteristics in Thunderstorms - Xu Dewang; Tan Yongbo (应用气象学报)
Characteristics of multi-point corona discharge have been a research hotspot in atmospheric electricity, and many studies concentrate on single-point or double-point corona discharge. However, characteristics of multi-point corona discharge are worthwhile to investigate because the presence of sharp points on the ground and their interactions. In order to study characteristics of multi-points corona discharge in thunderstorm environments, a two-dimensional time-varying corona discharge model is used to simulate the process of multi-point corona discharge, and sensitivity tests are conducted. Results show that, within a certain space, as the number of points increases, the total corona charge released by points gradually increases, and when the number of points increases to a certain level, the total corona charge remains basically unchanged. The growth will not continue as the number of points increases. When the points release corona charge, the corona current ranges from 0.84×10-5 μA to 2.24×10-5 μA.Under multi-point conditions, the relative position of the point, the distance between points, and the environmental electric field play an important role in whether the point can release corona charge, and the environmental electric field is the dominant factor. As the ambient electric field intensifies, the number of points releasing corona charges gradually rises. Under the same environmental electric field, as the distance between points increase, compared to the height of the points, each point is approximately an independent point, the interaction between points decreases, and points that can release corona charge also increase.Once points release corona charge, a suppressed electric field is generated by the corona charge at points. The suppressed electric field is influenced by the total corona charge present in the space, as well as the spatial distribution of that charge. When corona discharge reaches dynamic equilibrium, the suppressed electric field value can be calculated using the environmental electric field and the electric field distortion coefficient at the specified points. When the point distortion coefficient is unique, the suppression electric field at the point is linearly related to the environmental electric field. If the point does not release a corona charge, the suppression electric field at the point is nonlinearly related to the environmental electric field. The suppression electric field at the point is entirely generated by the corona charge released from other points. Its magnitude is influenced by the environmental electric field and the point's own distortion coefficient.